The Animals’ Point of View: Review of Chiara Mengozzi, ed. Outside the Anthropological Machine: Crossing the Human–Animal Divide and Other Exit Strategies - Krebber, André (Humanimalia, 2022)
Review of: Chiara Mengozzi, ed. Outside the Anthropological Machine: Crossing the Human–Animal Divide and Other Exit Strategies. Perspectives on the Non-Human in Literature and Culture. London: Routledge, 2021. vii + 283 pp., 23 b/w ill. £104.00 (hb); £29.59 (pb, eB)